Worktime control access, need and use in relation to work-home interference, fatigue, and job motivation - Nijp, Hylco H.; Beckers, Debby GJ; Kompier, Michiel AJ; van den Bossche, Seth NJ; Geurts, Sabine AE (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVE ': 'Worktime control (WTC) has been suggested as a tool to reduce employees’ work-home interference and fatigue and improve job motivation. The purpose of this study was twofold: (i) to examine the prevalence of employees’ need for, access to, and use of WTC, as well as the incongruence between need for and access to WTC (ie, mismatch); and (ii) to examine the associations of this mismatch and the use of WTC with employees’ work–home interference (WHI), fatigue and job motivation. ' ' METHODS ': 'Questionnaire data were collected among a large (N=2420) quasi-representative sample of Dutch employees. The prevalence of WTC need, access, use, and mismatch was assessed by means of descriptive statistics. Associations with employees’ outcomes were assessed by analyses of covariance. ' ' RESULTS ': 'The need for WTC was highly prevalent. For many employees, we observed a negative mismatch between access to and need for WTC (ie, access<need). A negative WTC mismatch was associated with relatively high levels of WHI and fatigue, and lower job motivation. The use of WTC was also highly prevalent, but no meaningful associations were found with the outcome variables. ' ' CONCLUSIONS ': 'It is relevant to examine WTC comprehensively, that is, to include measurements of employees’ need for and access to WTC and assess employees’ (mis)match between components of WTC. For practice, we recommend to introduce WTC on an organizational level and assess employees’ need for WTC on an individual basis.
Keywords: employees’ need; fatigue; job motivation; schedule control; well-being; work arrangement; work-home interference; work-life balance; working time; working time flexibility; worktime control; worktime control access